Realizability of tropical canonical divisors - Möller, Martin; Ulirsch, Martin; Werner, Annette (Journal of the European Mathematical Society : JEMS, 2021)
We use recent results by Bainbridge–Chen–Gendron–Grushevsky–Möller on compactifications of strata of abelian differentials to give a comprehensive solution to the realizability problem for effective tropical canonical divisors in equicharacteristic zero. Given a pair $(Γ, D)$ consisting of a stable tropical curve $Γ$ and a divisor $D$ in the canonical linear system on $Γ$, we give a purely combinatorial condition to decide whether there is a smooth curve $X$ over a non-Archimedean field whose stable reduction has $Γ$ as its dual tropical curve together with an effective canonical divisor $K_X$ that specializes to $D$.